1993
DOI: 10.1139/g93-005
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing of chromosome I from Saccharomyces cerevisiae: analysis of a 32 kb region between the LTE1 and SPO7 genes

Abstract: The DNA sequencing and preliminary functional analysis of a 32 kb section of yeast chromosome I has been completed. This region lies on the left arm of the chromosome between the LTE1 and SPO7 genes and contains 14 open reading frames (ORFs) positioned closely together, with an average spacing of approximately 350 nucleotides between coding regions. Three of these ORFs correspond to previously identified genes, a further three show significant homology with other proteins, while the remaining eight ORFs share … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Four microlitres of the 320-fold dilution were loaded. In the CYS3 promoter region, the sequence of this plasmid is identical to that published by Ono et al (1992) but differs by a 2 bp deletion from the sequence published by Ouellette et al (1993) at position -315 (our coordinates, see Figure 4).…”
Section: Dna Sequencingmentioning
confidence: 78%
“…Four microlitres of the 320-fold dilution were loaded. In the CYS3 promoter region, the sequence of this plasmid is identical to that published by Ono et al (1992) but differs by a 2 bp deletion from the sequence published by Ouellette et al (1993) at position -315 (our coordinates, see Figure 4).…”
Section: Dna Sequencingmentioning
confidence: 78%
“…8 (NCBI sequence ID 1419843)) lacks the four-cysteine [4Fe-4S] motif completely and presents an obvious exception to this consensus sequence. However, this sequence also encodes a putative mitochondrial leader sequence (28). Whether pairs of endonuclease III-like proteins, with and without [4Fe-4S] clusters, are present in other eukaryotic organisms and whether the non-Fe-S proteins are mitochondrial remains to be determined.…”
Section: Resultsmentioning
confidence: 99%
“…4). Comparison of the putative amino acid sequence with sequences in the GenBank database indicated that MDMIO was previously identified as an open reading frame adjacent to the SP07 gene on chromosome I and was designated FUN37(FUN=funedon unknown now) (Whyte et al, 1990) and as YAL010 (Ouellette et al, 1993). The Mdml0p amino acid sequence does not display significant similarities to other known proteins, common motifs for functional sites, or characteristic targeting sequences for subcellular localization.…”
Section: Isolation and Analysis Of The Mdmio Genementioning
confidence: 99%